Determinants of Health-Related Quality of Life in Taiwanese Middle-Aged Women Stroke Survivors. Issue 2 (March 2017) - Pai, Hsiang-Chu; Wu, Ming-Hsiu; Chang, Mei-Yueh
Abstract: Purpose: : Female stroke victims have a higher survival rate and experience a greater loss of quality of life than do male stroke victims. The aim of this study was to evaluate the determinants of health-related quality of life in middle-aged women stroke survivors. Design: : This study is a cross-sectional design. Methods: : This cross-sectional research uses a descriptive, prospective, and correlational study design to investigate the associations between latent variables. Participants included women stroke survivors, aged 45–65 years, who were patients at a medical center in Taiwan. Participants completed an interview and a six-part questionnaire comprising the Short-Form Health Survey (SF-36), National Institutes of Health Stroke Scale, Modified Rankin Scale, Burden Scale, Chinese Health Questionnaire, and five items that pertain to the survivor's cognitive appraisal of coping. Structural equation modeling (SEM), with the use of the partial least squares (PLS) method, was used to examine the proposed conceptual model. Findings: : A total of 48 dyad samples (48 female stroke survivors, mean age = 55.29; 48 caregivers, mean age = 42.71) participated in the study. Overall, women's physical functioning (PF; stroke severity), cognitive appraisal of coping, and caregiver's psychosocial functioning were the predictors, explaining 43.3% of the variance in women's health-related quality of life. Conclusions and Clinical Relevance: : We found that female stroke survivors' level of stroke severity and negative appraisal-impact of stroke are significant predictors of the stroke survivor's quality of life. In addition to assisting women in their PF rehabilitation, rehabilitation nurses also should help to develop survivors' self-care confidence as a means to avoid the recurrence of stroke.